Effects of Commercial Boifertilizers on Growth and Yield of Antimalarial Compounds of Artemi sia Annua - Aidah, Namuli; Engeu, Ogwang Patrick; Baptist, Tumuhairwe John; Ajayi, Clement; Joel, Bazira (International Journal of Plant & Soil Science, 2023)
Introduction: Artemisia annua is a medicinal plant grown by Ugandan farmers in Kabale and Kabarole. It is particularly used in preparation of antimalarial herbal teas used to control and prevent malaria. The content of these antimalarial compounds in A.annua (Anamed) grown in Uganda are low compared to cultivars in other countries but could be enhanced using economical, eco-friendly, and sustainable fertilizers (biofertilizers). Thus, the effect of commercially available biofertilizers in Uganda on A.annua antimalarial components was assessed. Methodology: Seven different commercially available biofertilizers containing nitrogen fixing strains and phosphate solubilizers obtained from the top biofertilizer distributors to Uganda (Shittah Agri and Biotech Pvt Ltd4 106 C22) and manufacturer (Kinyara Sugar Works Ltd.) were used. Their efficiency was assessed by measuring the vegetative growth characters and the content of flavonoids and artemisinin (using High Performance Liquid Chromatography, HPLC) and polysaccharides (using Ultra Violet visible, UV-vis spectrophotometer). Results: Though overall increase in growth was observed upon application of the biofertilizers, there was variation in the concentration of the antimalarial compounds. The highest kaempferol content and artemisinin content were observed in A. annua inoculated with Azotobacter spp. AZT (17.05 µg/ml and 1.43%) and Bacillus subtilis, BS (19.12 µg/ml, 1.42%) while the highest quercetin content was observed in A. annua inoculated with AZT (0.42 µg/ml) and Bacillus megaterium, BM (0.41 µg/ml). Additionally, fertilizers (biofertilizers and chemical fertilizers) decreased polysaccharide content. Conclusion: The findings demonstrate that application of commercially available biofertilizers in Uganda is beneficial in increasing concentration of artemisinin and flavonoids and thus can be utilized by Artemisia annua farmers in Uganda
Keywords: Artemisia annua; Biofertilizers; Flavonoids; Polysaccharides; Commercial; Artemisinin